2018
DOI: 10.1007/s00296-018-4108-z
|View full text |Cite
|
Sign up to set email alerts
|

Activity of rheumatoid arthritis correlates with oral inflammatory burden

Abstract: To study oral health in patients with rheumatoid arthritis (RA) with emphasis on disease activity and treatment of RA. In this prospective cohort study 81 RA patients [53 early untreated RA (EURA) and 28 chronic RA (CRA) patients with inadequate response to synthetic disease modifying antirheumatic drugs (DMARDs)], underwent rheumatological [Disease Activity Score (28-joint) DAS28] and dental examinations [Total Dental Index (TDI), Decayed Missing Filled Teeth (DMFT) and Decayed Missing Filled Surfaces (DMFS)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…The investigators included 53 untreated newly diagnosed rheumatoid arthritis patients (control group) and 28 chronic rheumatoid arthritis patients. The authors found a high frequency of caries in both groups, identifying a higher presence of xerostomia in patients with chronic RA (12). Some variables associated with the high frequency of dental caries in subjects with RA are:…”
Section: Dental Caries and Rheumatoid Arthritis (Ra)mentioning
confidence: 93%
See 3 more Smart Citations
“…The investigators included 53 untreated newly diagnosed rheumatoid arthritis patients (control group) and 28 chronic rheumatoid arthritis patients. The authors found a high frequency of caries in both groups, identifying a higher presence of xerostomia in patients with chronic RA (12). Some variables associated with the high frequency of dental caries in subjects with RA are:…”
Section: Dental Caries and Rheumatoid Arthritis (Ra)mentioning
confidence: 93%
“…Osteoarthritis in fingers and hands and 8. General osteoarthritis causing severe immobility in the patient (5)(6)(7)(8)(9)10,12,(31)(32)(33)(34).…”
Section: Dental Caries and Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, S.mutans was significantly higher in RA patients and indices for oral inflammatory burden and disease were associated with serologic markers for RA. Furthermore, the oral inflammatory burden was significantly higher in early untreated RA when compared to chronic RA [ 82 ]. RA is a risk factor for both caries and periodontal disease [ 3 ].…”
Section: Discussionmentioning
confidence: 99%